Damping rubber material as well as preparation method and application thereof

By using specific ratios of nitrile rubber and styrene butadiene rubber in the shock absorbing rubber material, combined with carbon black, white carbon black, silane modified mica and metal reinforced materials, the problem of unstable elastic modulus of traditional shock absorbing rubber under high temperature and dynamic pressure is solved, and higher strength, toughness and heat resistance are achieved, ensuring high-precision rolling pressure of the battery pole sheet and improving battery performance.

CN119859329AInactive Publication Date: 2025-04-22CHUNFENG YINXING RUBBER ROLLER CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510345225.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In traditional roller pressing processes, it is difficult for shock-absorbing rubber to maintain a stable elastic modulus under dynamic pressure and high temperatures, resulting in uneven thickness of the pole sheet and falling off the active material, affecting battery performance and safety.

Method used

By controlling the raw material components and ratio of shock-absorbing rubber materials, nitrile rubber and styrene butadiene rubber are used as the rubber matrix, and carbon black, white carbon black, silane modified mica and metal reinforcement materials are added to improve the strength, toughness and heat resistance of the material.

Benefits of technology

It significantly improves the comprehensive performance of shock-absorbing rubber materials, can effectively suppress vibration during rolling, ensure high-precision processing of the pole sheet, and extend the cycle life and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of rolling rubber materials, and particularly discloses a damping rubber material as well as a preparation method and application thereof. The damping rubber material comprises nitrile rubber, butadiene styrene rubber, a composite filler, a metal reinforcing material and an auxiliary agent, the composite filler comprises carbon black, white carbon black, silane modified mica and silicon dioxide aerogel. Nitrile rubber and butadiene styrene rubber are compounded as a rubber matrix, so that the processability and high and low temperature resistance of the rubber material can be improved; the carbon black has excellent tear resistance and wear resistance, and the white carbon black can improve the strength and hardness of the rubber material; the mica is an aluminosilicate mineral with a layered structure, the stress effect between layers is small, and the mutual acting force between the layers can be relieved when the mica is subjected to pressure; the silane modified mica is adopted, so that the compatibility of the mica and an organic material can be improved; the metal reinforcing material can improve the overall strength and bearing capacity of the damping rubber material. The damping rubber material has excellent strength, toughness, heat resistance and performance stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rolled rubber materials, and in particular to a shock-absorbing rubber material and a preparation method and application thereof. Background Art

[0002] During the battery production process, the rolling process rolls the pole pieces coated with active materials to achieve the specified thickness and compaction density, thereby ensuring that the battery has good performance and consistency. Pole piece rolling is a key process to improve energy density and the bonding strength of electrode materials, which directly affects the cycle life and safety of the battery. In the traditional rolling process, the shock-absorbing rubber needs to maintain a stable elastic modulus under dynamic pressure (20t level) and high temperature (60℃~80℃) conditions to avoid pole piece thickness errors and active material shedding.

[0003] At present, the traditional rigid connection method is generally used in battery pole piece rolling equipment, that is, the roller is directly installed on the frame. When this structure is in operation, the vibration generated during the operation of the equipment, especially the high-frequency vibration, will be directly transmitted to the pole piece. On the one hand, the vibration interferes with the stability of the rolling process, making it difficult to maintain uniform thickness of the pole piece during the rolling process, which in turn affects the consistency of the compaction density of the pole piece. For example, in some high-speed rolling equipment, the deviation of the pole piece thickness caused by vibration can reach ±5μm, which seriously exceeds the industry standard requirement for the pole piece thickness deviation to be controlled at ±2μm. On the other hand, large vibrations can cause the active material particles on the surface of the pole piece to shift or even fall off, destroying the microstructure of the pole piece. Scanning electron microscopy observations found that the bonding force between the active material and the current collector was weakened on the pole piece surface affected by vibration, which is easy to cause problems such as increased internal resistance of the battery and accelerated capacity decay during the battery charge and discharge cycle.

[0004] To solve these problems, some existing technologies attempt to install some simple shock-absorbing devices, such as ordinary rubber pads, on the equipment frame. However, the shock-absorbing performance of ordinary rubber pads is limited, and it is difficult to adapt to the complex and changeable vibration frequency and amplitude during the rolling process of battery pole pieces. In actual production, with the adjustment of rolling speed and pressure, the vibration situation will change significantly. Ordinary rubber pads cannot suppress the vibration under different working conditions in a timely and effective manner, and cannot fundamentally meet the needs of high-precision rolling of battery pole pieces. Therefore, the development of a high-performance shock-absorbing rubber specifically for rolling of battery pole pieces to effectively suppress vibrations during rolling and ensure high-precision processing of pole pieces has become an important issue that needs to be urgently addressed in the current battery production field. Summary of the invention

[0005] In view of the problem that the comprehensive performance of rolled rubber materials cannot meet the use requirements, the present invention provides a shock-absorbing rubber material and a preparation method and application thereof. By controlling the raw material components and proportions of the shock-absorbing rubber material, the strength, toughness, heat resistance and performance stability of the shock-absorbing rubber material are significantly improved.

[0006] In order to solve the above technical problems, the technical solution provided by the present invention is: In a first aspect, the present invention provides a shock-absorbing rubber material, comprising the following raw materials in parts by mass: 45 to 55 parts of nitrile rubber, 10 to 18 parts of styrene-butadiene rubber, 35 to 45 parts of composite fillers, 5 to 10 parts of metal reinforcement materials and 14 to 22 parts of additives; the composite fillers include carbon black, white carbon black, silane-modified mica and silica aerogel.

[0007] Compared with the prior art, the shock-absorbing rubber material provided by the present invention uses a specific ratio of nitrile rubber and styrene-butadiene rubber as a rubber matrix. The nitrile rubber has excellent oil resistance and high wear resistance, heat resistance and strong adhesion. The processing performance of styrene-butadiene rubber is close to that of natural rubber, and it has better wear resistance, heat resistance, aging resistance and vulcanization speed. When mixed with nitrile rubber, the advantages of the two can be combined to improve the processing performance, wear resistance and high and low temperature resistance of the rubber material. Carbon black has excellent tear resistance and wear resistance. White carbon black is used as a filler to improve the strength and hardness of the rubber material. Mica is a layered aluminum silicate mineral, and its crystal structure is a monoclinic system. It has a hexagonal sheet or plate shape, with the layers bonded by van der Waals forces. The layers are composed of silicon-oxygen tetrahedrons and aluminum-oxygen octahedrons to form a strong covalent bond network. The stress between layers is small, and the interaction force between layers can be effectively relieved when under pressure. There are a large number of exposed hydroxyl groups and silicon-oxygen bonds on the surface of mica, resulting in uneven surface charge distribution and strong polarity. The polar surface easily adsorbs water molecules and charged ions, causing mica to easily aggregate in a humid environment. The use of silane-modified mica can greatly improve its compatibility with organic materials (rubber matrix). The addition of a specific amount of metal reinforcement material can further improve the overall strength and bearing capacity of the shock-absorbing rubber material.

[0008] The present invention improves the compatibility between the raw material components by limiting the raw materials and their proportions of the shock-absorbing rubber material, so that the raw material components have a synergistic effect, thereby greatly improving the comprehensive performance of the shock-absorbing rubber material.

[0009] Preferably, the mass content of acrylonitrile in the nitrile rubber is 28% to 34%.

[0010] The invention can better balance the oil resistance, low temperature elasticity and hardness of the shock-absorbing rubber material by limiting the content of acrylonitrile.

[0011] Further preferably, the nitrile rubber includes at least one of NBR-3350 or NBR-3345.

[0012] Preferably, the styrene-butadiene rubber includes at least one of SBR-1500 and SBR-1502.

[0013] Preferably, the composite filler comprises: 20 to 25 parts of carbon black, 5 to 8 parts of white carbon black, 5 to 8 parts of silane-modified mica and 3 to 6 parts of silica aerogel.

[0014] White carbon black, mica and fumed silica aerogel are all silicate fillers. Compounding carbon black and silicate fillers in a specific proportion can bring into play the synergistic effect of each filler, which not only further improves the strength of the rubber material, but also improves the stability of its high-temperature elastic modulus and reduces the thermal expansion coefficient of the rubber material.

[0015] Preferably, the carbon black includes at least one of N550 or N660.

[0016] Preferably, the preparation method of the silane-modified mica comprises the following steps: The silane coupling agent and mica are added into a solvent to carry out coupling reaction to obtain silane-modified mica.

[0017] Mica is a rigid particle that can significantly improve the mechanical strength of rubber materials. However, its compatibility with the rubber matrix is ​​extremely poor. Direct addition will not only fail to improve its mechanical strength, but will also cause stratification due to poor dispersibility, thereby reducing the overall performance of the shock-absorbing rubber material. Mica is an aluminum silicate powder, a polar, water-insoluble inorganic mineral. It has poor compatibility when added to a non-polar or weakly polar polymer organic system (rubber matrix). Due to the small particle size and high surface energy of mica powder, the particles are easy to agglomerate, which is even more unfavorable for compatible dispersion in organic systems.

[0018] The present invention adopts a silane coupling agent to modify mica, which can improve the suspension stability of mica, improve the fusion of the powder material surface with other components, improve the homogeneity of mica dispersion, and further exert the shock absorption and reinforcement effects of mica in rubber materials.

[0019] Further preferably, the silane coupling agent includes KH-550.

[0020] More preferably, the solvent is at least one of ethanol or water.

[0021] Further preferably, the mass volume ratio of the silane coupling agent, mica and solvent is (5-10) g:100 g:(600-800) mL.

[0022] More preferably, the coupling reaction temperature is 70° C. to 90° C., and the reaction time is 45 min to 60 min.

[0023] For example, after the coupling reaction is completed, the process further includes: solid-liquid separation, washing and drying the solid.

[0024] Preferably, the method for preparing the composite filler comprises the following steps: Carbon black, white carbon black, silane-modified mica and silica aerogel are mixed at 50° C. to 80° C. to obtain a composite filler.

[0025] Preferably, the metal reinforcement material comprises cold-drawn steel wire.

[0026] Preferably, the metal reinforcement material is in the shape of a mesh and is made of carbon steel or stainless steel.

[0027] For example, the material of the cold-drawn steel wire is Q235 steel or 304 stainless steel.

[0028] Preferably, the metal reinforcement material is located in the middle of the shock-absorbing rubber material.

[0029] In the present invention, the structure of the shock-absorbing rubber material is "rubber material-metal reinforcement material-rubber material". The outer rubber material has the function of absorbing high-frequency vibration, the middle metal reinforcement material has the function of dispersing the roller pressure, and the inner rubber material has the function of buffering the stress concentration at the edge of the pole piece. This structural design can effectively reduce the crack formation rate and dark mark defect rate on the surface of the electrode material, and effectively reduce the amplitude of the roller during use.

[0030] Preferably, the auxiliary agent includes: 5 to 8 parts of plasticizer, 1.5 to 2.5 parts of antioxidant, 0.5 to 1 part of paraffin, 1 to 2 parts of lubricant, 1.5 to 2.5 parts of vulcanizing agent, 1 to 1.8 parts of vulcanization accelerator and 3 to 5 parts of activator.

[0031] Further preferably, the plasticizer includes at least one of dioctyl phthalate (DOP) or dioctyl sebacate (DOS).

[0032] Further preferably, the antioxidant comprises 4010NA and RD in a mass ratio of (1.5-2.5):1.

[0033] Further preferably, the lubricant comprises stearic acid.

[0034] Further preferably, the vulcanizing agent includes sulfur.

[0035] More preferably, the vulcanization accelerator includes at least one of a sulfonamide accelerator or a thiazole accelerator.

[0036] More preferably, the vulcanization accelerator includes at least one of N-cyclohexyl-2-benzothiazole sulfenamide (CZ) or dibenzothiazyl disulfide (DM).

[0037] Further preferably, the activator comprises zinc oxide.

[0038] In a second aspect, the present invention provides a method for preparing the shock-absorbing rubber material, comprising the following steps: S1, weighing various raw materials according to the designed ratio, adding nitrile rubber, styrene butadiene rubber, composite filler, plasticizer, antioxidant, paraffin and lubricant into an internal mixer for internal mixing to obtain a rubber mixture; S2, adding the mixed rubber, vulcanizing agent, vulcanization accelerator and activator into an open mixer, thinning in the form of triangular packages, and sheeting through a calender to obtain a rubber sheet; S3, placing a metal reinforcement material between the two rubber sheets to form a "rubber sheet-metal reinforcement material-rubber sheet" structure, applying pressure using a flat vulcanizing agent, and vulcanizing to obtain a shock-absorbing rubber material.

[0039] The preparation method of the shock-absorbing rubber material provided by the present invention comprises the following steps: firstly, mixing the raw materials by internal mixing and open mixing to make the raw materials uniform, and then producing sheets by a calender to obtain rubber sheets; then, stacking and pressing the sheets according to the structural design to obtain a primary product, and finally vulcanizing the shock-absorbing rubber material. The whole process is simple to operate, the raw materials are cheap and easy to obtain, and the shock-absorbing rubber material has good market application value.

[0040] Preferably, in S1, the temperature of the internal mixing is 110° C. to 130° C., the speed of the internal mixer is 40 rpm to 60 rpm, and the internal mixing time is 15 min to 20 min.

[0041] Preferably, in S2, the roller temperature of the mixing mill is 40° C. to 60° C., and the roller distance is 2 mm to 3 mm; and the number of thin passes is 3 to 4 times.

[0042] For example, in S3, before placing the metal reinforcement material, it is necessary to use acetone or isopropyl alcohol to clean the surface of the metal reinforcement material to remove impurities such as oil and oxide layer on the surface to ensure the cleanliness of the bonding interface (residual contaminants < 0.1 mg / m 2 )‌.

[0043] Preferably, in S3, before placing the metal reinforcement material, the method further includes: sandblasting the metal reinforcement material to make the surface roughness of the metal reinforcement material ≥6.3 μm.

[0044] Further preferably, in S3, the particle size of the sand used for the sand blasting is 0.5 mm to 1.2 mm, and the hardness of the sand is ≥HRC60.

[0045] The invention performs sandblasting on the metal reinforcement material, thereby enhancing the mechanical bite force between the rubber sheet and the metal reinforcement material.

[0046] Preferably, in S3, before placing the metal reinforcement material, the step further includes: spraying an adhesive on the surface of the metal reinforcement material.

[0047] The present invention sprays adhesive on the surface of the metal reinforcement material, which can better ensure the bonding effect between the rubber sheet and the metal reinforcement material, avoid interlayer peeling under external force or during use, and extend the service life.

[0048] For example, in S3, the adhesive may be a Chemlok series adhesive (such as Chemlok 205 or Chemlok 220), the adhesive may be coated with a thickness of 5 μm to 10 μm, and may be pre-cured at 80° C. to 100° C. for 10 min to 15 min.

[0049] Preferably, in S3, the pressure of the applied pressure is 0.5 MPa~1 MPa.

[0050] Preferably, in S3, the vulcanization temperature is 150° C. to 180° C., the vulcanization pressure is 10 MPa to 15 MPa, and the vulcanization time is 20 min to 30 min.

[0051] For example, in S3, after the vulcanization is completed, the process further includes: maintaining the pressure and cooling the temperature to below 60° C. and then demolding to avoid interlayer peeling caused by thermal stress.

[0052] In a third aspect, the present invention provides a rubber material for rolling battery electrodes, including the shock-absorbing rubber material. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0054] In the present invention, unless otherwise specified, all materials are commercially available products.

[0055] Example 1 The present embodiment provides a shock-absorbing rubber material, comprising the following raw materials in parts by mass: 50 parts of nitrile rubber (NBR-3350), 14 parts of styrene-butadiene rubber (SBR-1500), 40 parts of composite filler, 8 parts of metal reinforcement material (evenly distributed mesh cold-drawn steel wire Q235 steel) and 17.6 parts of additives.

[0056] The composite filler has the following raw materials in parts by mass: 22 parts of carbon black (N550), 7 parts of white carbon black, 6 parts of silane-modified mica and 5 parts of silica aerogel.

[0057] The additives include the following raw materials in parts by mass: 6 parts of plasticizer (DOP), 2 parts of antioxidant (4010NA and RD with a mass ratio of 5:1), 0.7 parts of paraffin, 1.5 parts of stearic acid, 2 parts of sulfur, 1.4 parts of vulcanization accelerator (CZ) and 4 parts of zinc oxide.

[0058] The preparation method of the shock-absorbing rubber material comprises the following steps: Sa, KH-550 and mica were added to 90% (v / v) ethanol aqueous solution, the mass volume ratio of KH-550, mica and ethanol aqueous solution was 8g:100g:700mL, coupling reaction was carried out at 80°C, the temperature was kept for 55min, solid-liquid separation was performed, the solid was washed and dried, and silane-modified mica was obtained.

[0059] Sb, weigh each raw material according to the designed ratio, mix carbon black, white carbon black, silane-modified mica and silica aerogel at 70°C to obtain a composite filler.

[0060] Sc, add nitrile rubber, styrene butadiene rubber, composite filler, plasticizer, antioxidant, paraffin and stearic acid into an internal mixer, mix at 120°C for 18 min, and the speed of the internal mixer is 50 rpm to obtain a mixed rubber.

[0061] Sd, add the mixed rubber, sulfur, vulcanization accelerator and zinc oxide into an open mill, the roller temperature is 50°C, the roller distance is 2mm, and after thinning through three times in the form of a triangular package, it is discharged through a calender to obtain a rubber sheet.

[0062] Se, after the surface of the metal reinforcement material is cleaned, it is sandblasted, the particle size of the sand is 0.8mm, the hardness of the sand is ≥HRC60, and the surface roughness of the metal reinforcement material is 6.5μm.

[0063] It should be noted that this embodiment does not limit the sequence of steps Se and Sa~Sd.

[0064] Sf, put the metal reinforcement material between two rubber sheets to form a "rubber sheet-metal reinforcement material-rubber sheet" structure, use a flat vulcanizer to apply pressure (pressure is 0.8MPa), vulcanize at 170℃ for 25min, and the vulcanization pressure is 13MPa; then maintain the pressure and cool to below 60℃ before demolding to obtain a shock-absorbing rubber material.

[0065] Example 2 The present embodiment provides a shock-absorbing rubber material, comprising the following raw materials in parts by mass: 45 parts of nitrile rubber (NBR-3345), 18 parts of styrene-butadiene rubber (SBR-1502), 36 parts of composite filler, 7 parts of metal reinforcement material (evenly distributed mesh cold-drawn steel wire 304 stainless steel) and 18.5 parts of additives.

[0066] The composite filler has the following raw materials in parts by mass: 20 parts of carbon black (N660), 8 parts of white carbon black, 5 parts of silane-modified mica and 3 parts of silica aerogel.

[0067] The additives include the following raw materials in parts by mass: 7 parts of plasticizer (DOS), 1.5 parts of antioxidant (4010NA and RD with a mass ratio of 2.5:1), 1 part of paraffin, 1.5 parts of stearic acid, 2 parts of sulfur, 1.5 parts of vulcanization accelerator (DM) and 4 parts of zinc oxide.

[0068] The preparation method of the shock-absorbing rubber material comprises the following steps: Sa, KH-550 and mica are added to water, the mass volume ratio of KH-550, mica and water is 10g:100g:800mL, coupling reaction is carried out at 90°C, heat preservation for 47min, solid-liquid separation, solid is taken for washing and drying, and silane-modified mica is obtained.

[0069] Sb, weigh each raw material according to the designed ratio, mix carbon black, white carbon black, silane-modified mica and silica aerogel at 80°C to obtain a composite filler.

[0070] Sc, add nitrile rubber, styrene-butadiene rubber, composite filler, plasticizer, antioxidant, paraffin and stearic acid into an internal mixer, mix at 120°C for 17 min, and the speed of the internal mixer is 40 rpm to obtain a mixed rubber.

[0071] Sd, add the mixed rubber, sulfur, vulcanization accelerator and zinc oxide into an open mill, the roller temperature is 40°C, the roller distance is 2mm, and after thinning through 4 times in the form of a triangular package, it is discharged through a calender to obtain a rubber sheet.

[0072] Se, after the surface of the metal reinforcement material was cleaned, the adhesive (Chemlok 205) was sprayed on the surface of the metal reinforcement material, the coating thickness of the adhesive was 6 μm, and it was pre-cured at 80 °C for 15 min.

[0073] It should be noted that this embodiment does not limit the sequence of steps Se and Sa~Sd.

[0074] Sf, put the metal reinforcement material between two rubber sheets to form a "rubber sheet-metal reinforcement material-rubber sheet" structure, use a flat vulcanizer to apply pressure (pressure is 0.7MPa), vulcanize at 160℃ for 25min, and the vulcanization pressure is 12MPa; then maintain the pressure and cool to below 60℃ before demolding to obtain a shock-absorbing rubber material.

[0075] Example 3 The present embodiment provides a shock-absorbing rubber material, comprising the following raw materials in parts by mass: 48 parts of nitrile rubber (NBR-3350), 15 parts of styrene-butadiene rubber (SBR-1500), 38 parts of composite filler, 5 parts of metal reinforcing material (evenly distributed mesh cold-drawn steel wire Q235 steel) and 15.1 parts of additives.

[0076] The composite filler has the following raw materials in parts by mass: 25 parts of carbon black (N550), 5 parts of white carbon black, 5 parts of silane-modified mica and 3 parts of silica aerogel.

[0077] The additives include the following raw materials in parts by mass: 5 parts of plasticizer (DOP), 2 parts of antioxidant (4010NA and RD with a mass ratio of 1.5:1), 0.8 parts of paraffin, 1 part of stearic acid, 1.5 parts of sulfur, 1.8 parts of vulcanization accelerator (CZ) and 3 parts of zinc oxide.

[0078] The preparation method of the shock-absorbing rubber material comprises the following steps: Sa, KH-550 and mica were added to a 50% (v / v) ethanol aqueous solution, the mass volume ratio of KH-550, mica and ethanol aqueous solution was 7g:100g:720mL, the coupling reaction was carried out at 80°C, the temperature was kept for 50min, the solid-liquid separation was performed, the solid was washed and dried, and the silane-modified mica was obtained.

[0079] Sb, weigh each raw material according to the designed ratio, mix carbon black, white carbon black, silane-modified mica and silica aerogel at 60°C to obtain a composite filler.

[0080] Sc, add nitrile rubber, styrene-butadiene rubber, composite filler, plasticizer, antioxidant, paraffin and stearic acid into an internal mixer, mix at 130°C for 15 min, and the speed of the internal mixer is 60 rpm to obtain a mixed rubber.

[0081] Sd, add the mixed rubber, sulfur, vulcanization accelerator and zinc oxide into an open mill, the roller temperature is 50°C, the roller distance is 3mm, and after thinning through three times in the form of a triangular package, it is discharged through a calender to obtain a rubber sheet.

[0082] Se, after the surface of the metal reinforcement material is cleaned, the adhesive (Chemlok 220) is sprayed on the surface of the metal reinforcement material, the coating thickness of the adhesive is 10 μm, and it is pre-cured at 100 °C for 10 min.

[0083] It should be noted that this embodiment does not limit the sequence of steps Se and Sa~Sd.

[0084] Sf, put the metal reinforcement material between two rubber sheets to form a "rubber sheet-metal reinforcement material-rubber sheet" structure, use a flat vulcanizer to apply pressure (pressure is 0.5MPa), vulcanize at 153℃ for 30min, and the vulcanization pressure is 10MPa; then maintain the pressure and cool to below 60℃ before demolding to obtain a shock-absorbing rubber material.

[0085] Example 4 The present embodiment provides a shock-absorbing rubber material, comprising the following raw materials in parts by mass: 55 parts of nitrile rubber (NBR-3345), 10 parts of styrene-butadiene rubber (SBR-1500 and SBR-1502 in equal proportions by mass), 43 parts of composite filler, 10 parts of metal reinforcing material (uniformly distributed mesh cold-drawn steel wire 304 stainless steel) and 21.5 parts of additives.

[0086] The composite filler has the following raw materials in parts by weight: 23 parts of carbon black (N550 and N660 in equal weight ratio), 6 parts of white carbon black, 8 parts of silane-modified mica and 6 parts of silica aerogel.

[0087] The additives include the following raw materials in parts by mass: 8 parts of plasticizer (DOP and DOS in equal mass ratio), 2.5 parts of antioxidant (4010NA and RD in a mass ratio of 2:1), 0.5 parts of paraffin, 2 parts of stearic acid, 2.5 parts of sulfur, 1 part of vulcanization accelerator (CZ and DM in equal mass ratio) and 5 parts of zinc oxide.

[0088] The preparation method of the shock-absorbing rubber material comprises the following steps: Sa, KH-550 and mica are added to ethanol, the mass volume ratio of KH-550, mica and ethanol is 5g:100g:600mL, coupling reaction is carried out at 70°C, heat preservation for 60min, solid-liquid separation, solid is taken for washing and drying, and silane-modified mica is obtained.

[0089] Sb, weigh each raw material according to the designed ratio, mix carbon black, white carbon black, silane-modified mica and silica aerogel at 50°C to obtain a composite filler.

[0090] Sc, add nitrile rubber, styrene butadiene rubber, composite filler, plasticizer, antioxidant, paraffin and stearic acid into an internal mixer, mix at 110°C for 20 min, and the speed of the internal mixer is 50 rpm to obtain a mixed rubber.

[0091] Sd, add the mixed rubber, sulfur, vulcanization accelerator and zinc oxide into an open mill, the roller temperature is 60°C, the roller distance is 3mm, and after thinning through 4 times in the form of a triangular package, it is discharged through a calender to obtain a rubber sheet.

[0092] Se, after the surface of the metal reinforcement material is cleaned, it is sandblasted, the particle size of the sand is 1.2 mm, the hardness of the sand is ≥HRC60, and the surface roughness of the metal reinforcement material is 6.6 μm.

[0093] It should be noted that this embodiment does not limit the sequence of steps Se and Sa~Sd.

[0094] Sf, put the metal reinforcement material between two rubber sheets to form a "rubber sheet-metal reinforcement material-rubber sheet" structure, use a flat vulcanizer to apply pressure (pressure is 1MPa), vulcanize at 180℃ for 20min, and the vulcanization pressure is 15MPa; then maintain the pressure and cool to below 60℃ before demolding to obtain a shock-absorbing rubber material.

[0095] Comparative Example 1 This comparative example provides a shock-absorbing rubber material, the raw material components are similar to those of Example 1, except that the styrene-butadiene rubber (SBR-1500) is replaced with an equal mass of nitrile rubber (NBR-3350), that is, the mass fraction of the nitrile rubber is 64 parts. The remaining conditions are the same as those of Example 1 and will not be described in detail.

[0096] The preparation method of the shock-absorbing rubber material is similar to that of Example 1, except that the addition of styrene-butadiene rubber is omitted in Sc. The remaining steps are the same as those of Example 1 and will not be described in detail.

[0097] Comparative Example 2 This comparative example provides a shock-absorbing rubber material, and the raw material components are similar to those in Example 1, except that nitrile rubber (NBR-3350) is 35 parts and styrene-butadiene rubber (SBR-1500) is 29 parts. The remaining conditions are the same as those in Example 1 and will not be described in detail.

[0098] The preparation method of the shock-absorbing rubber material is the same as that of Example 1 and will not be described in detail.

[0099] Comparative Example 3 This comparative example provides a shock-absorbing rubber material, the raw material components are similar to those of Example 1, and the only difference is that the styrene-butadiene rubber (SBR-1500) is replaced by natural rubber (SVR-3L) of the same quality. The remaining conditions are the same as those of Example 1 and will not be repeated.

[0100] The preparation method of the shock-absorbing rubber material is similar to that of Example 1, except that in Sc, the styrene-butadiene rubber is replaced by natural rubber. The remaining steps are the same as those of Example 1 and will not be described in detail.

[0101] Comparative Example 4 This comparative example provides a shock-absorbing rubber material, the raw material components are similar to those of Example 1, and the only difference is that: no metal reinforcing material is contained. The other conditions are the same as those of Example 1 and will not be repeated.

[0102] The preparation method of the shock-absorbing rubber material comprises the following steps: Sa~Sd are the same as those in Example 1 and will not be described in detail.

[0103] Se, stack two rubber sheets, use a flat vulcanizer to apply pressure (pressure is 0.8MPa), vulcanize at 170℃ for 25min, and the vulcanization pressure is 13MPa; then maintain the pressure and cool to below 60℃ before demolding to obtain a shock-absorbing rubber material.

[0104] Comparative Example 5 This comparative example provides a shock-absorbing rubber material, the raw material components are similar to those of Example 2, except that in the composite filler, the silane-modified mica and the silica aerogel are replaced by white carbon black of equal mass, that is, the mass fraction of white carbon black is 16 parts. The other conditions are the same as those of Example 2 and will not be described in detail.

[0105] The preparation method of the shock-absorbing rubber material is similar to that of Example 2, except that step Sa is omitted, and the addition of silane-modified mica and silica aerogel is omitted in step Sb. The remaining steps are the same as those of Example 2 and will not be described in detail.

[0106] Comparative Example 6 This comparative example provides a shock-absorbing rubber material, the raw material components are similar to those of Example 2, except that in the composite filler, the silica aerogel is replaced with white carbon black of the same mass, that is, the mass fraction of white carbon black is 11 parts. The other conditions are the same as those of Example 2 and will not be repeated.

[0107] The preparation method of the shock-absorbing rubber material is similar to that of Example 2, except that the addition of silica aerogel is omitted in Sb. The remaining steps are the same as those of Example 2 and will not be described in detail.

[0108] Comparative Example 7 This comparative example provides a shock-absorbing rubber material, the raw material components are similar to those of Example 2, and the only difference is that in the composite filler, the silane-modified mica is replaced with talcum powder of the same mass. The other conditions are the same as those of Example 2 and will not be repeated.

[0109] The preparation method of the shock-absorbing rubber material is similar to that of Example 2, except that step Sa is omitted and talcum powder is used to replace silane-modified mica in Sb. The remaining steps are the same as those of Example 2 and will not be described in detail.

[0110] Comparative Example 8 This comparative example provides a shock-absorbing rubber material, the raw material components are similar to those of Example 2, and the only difference is that in the composite filler, the silane-modified mica is replaced with mica of the same mass (ie, the mica is not subjected to silane modification treatment). The remaining conditions are the same as those of Example 2 and will not be repeated.

[0111] The preparation method of the shock-absorbing rubber material is similar to that of Example 2, except that step Sa is omitted and the silane-modified mica is replaced by mica in Sb. The remaining steps are the same as those of Example 2 and will not be described in detail.

[0112] Performance Testing ‌ Bonding strength test‌: The tensile test verifies that the interface strength between the rubber and the metal reinforcement material in the shock-absorbing rubber material provided in Examples 1 to 4 is ≥ 6 MPa, meeting the anti-peeling requirement under a dynamic load of 20 t. ‌

[0113] The shock-absorbing rubber materials provided in Examples 1 to 4 and Comparative Examples 1 to 8 were respectively subjected to relevant performance tests, the tensile strength test and the elongation at break test were performed according to the reference standard GB / T 528-2009, the dynamic mechanical properties (including elastic modulus) test was performed according to the reference standard GB / T 16465-2008, the hardness test was performed according to the reference standard GB / T 531.1-2008, the wear resistance test was performed according to the reference standard GB / T9867-2008, the compression permanent deformation test at room temperature and high temperature (80°C) was performed according to the reference standard GB / T 7759-2015, and the aging performance (7d hot air aging) test was performed according to the reference standard GB / T 3512-2014. The test results are shown in Tables 1 and 2.

[0114] Table 1 Performance test results of the shock absorbing rubber materials of the embodiments and comparative examples 1

[0115] Table 2 Performance test results of the shock absorbing rubber materials of the embodiments and comparative examples

[0116] It can be seen from the table that the shock-absorbing rubber material provided by the embodiment of the present invention has excellent mechanical strength, elasticity, hardness, wear resistance and anti-aging performance, and can fully meet the performance requirements of the rubber material during battery pole sheet rolling. Compared with the embodiments, after the components or dosage of the rubber matrix are changed in Comparative Examples 1 to 3, the wear resistance, aging resistance and other properties are all reduced; after the metal reinforcement material is omitted in Comparative Example 4, its mechanical strength is significantly reduced; after the raw material components of the composite filler are changed in Comparative Examples 5 to 8, the compatibility between the composite filler and other raw materials is deteriorated, the dispersion of the filler is relatively deteriorated, and it is difficult to exert the interaction between the raw materials of the fillers, resulting in different degrees of decline in the comprehensive performance of the shock-absorbing rubber material.

[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A shock-absorbing rubber material, characterized in that: The invention comprises the following raw materials in parts by weight: 45 to 55 parts of nitrile rubber, 10 to 18 parts of styrene-butadiene rubber, 35 to 45 parts of composite fillers, 5 to 10 parts of metal reinforcing materials and 14 to 22 parts of additives; the composite fillers comprise carbon black, white carbon black, silane-modified mica and silica aerogel.

2. The shock-absorbing rubber material according to claim 1, characterized in that: The mass content of acrylonitrile in the nitrile rubber is 28% to 34%.

3. The shock-absorbing rubber material according to claim 1, characterized in that: The composite filler comprises: 20 to 25 parts of carbon black, 5 to 8 parts of white carbon black, 5 to 8 parts of silane-modified mica and 3 to 6 parts of silica aerogel; The auxiliary agent comprises: 5 to 8 parts of plasticizer, 1.5 to 2.5 parts of antioxidant, 0.5 to 1 part of paraffin, 1 to 2 parts of lubricant, 1.5 to 2.5 parts of vulcanizing agent, 1 to 1.8 parts of vulcanization accelerator and 3 to 5 parts of activator.

4. The shock-absorbing rubber material according to claim 1 or 3, characterized in that: The preparation method of the silane-modified mica comprises the following steps: Adding a silane coupling agent and mica into a solvent to carry out a coupling reaction to obtain silane-modified mica; The preparation method of the composite filler comprises the following steps: Carbon black, white carbon black, silane-modified mica and silica aerogel are mixed at 50° C. to 80° C. to obtain a composite filler.

5. The shock-absorbing rubber material according to claim 4, characterized in that: The silane coupling agent includes KH-550, and the solvent is at least one of ethanol or water; The mass volume ratio of the silane coupling agent, mica and solvent is (5-10) g:100 g:(600-800) mL; The temperature of the coupling reaction is 70°C to 90°C, and the reaction time is 45min to 60min.

6. The shock-absorbing rubber material according to claim 1, characterized in that: The metal reinforcement material comprises cold-drawn steel wire, and the shape of the metal reinforcement material is a mesh; The metal reinforcement material is located in the middle of the shock-absorbing rubber material.

7. The method for preparing the shock-absorbing rubber material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, weighing various raw materials according to the designed ratio, adding nitrile rubber, styrene butadiene rubber, composite filler, plasticizer, antioxidant, paraffin wax and lubricant into an internal mixer for internal mixing to obtain a mixed rubber; S2, adding the mixed rubber, vulcanizing agent, vulcanization accelerator and activator into an open mixer, thinning in the form of triangular packages, and sheeting through a calender to obtain a rubber sheet; S3, placing a metal reinforcement material between the two rubber sheets to form a "rubber sheet-metal reinforcement material-rubber sheet" structure, applying pressure using a flat vulcanizing agent, and vulcanizing to obtain a shock-absorbing rubber material.

8. The method for preparing a shock-absorbing rubber material according to claim 7, characterized in that: In S1, the temperature of the internal mixing is 110°C to 130°C, the speed of the internal mixer is 40rpm to 60rpm, and the internal mixing time is 15min to 20min; In S2, the roller temperature of the open mill is 40°C to 60°C, the roller distance is 2mm to 3mm; the number of thin passes is 3 to 4 times; In S3, the pressure of the applied pressure is 0.5MPa~1MPa; In S3, the vulcanization temperature is 150° C. to 180° C., the vulcanization pressure is 10 MPa to 15 MPa, and the vulcanization time is 20 min to 30 min.

9. The method for preparing a shock-absorbing rubber material according to claim 7, characterized in that: In S3, before placing the metal reinforcement material, the process further includes: sandblasting the metal reinforcement material to make the surface roughness of the metal reinforcement material ≥6.3 μm; the particle size of the sand used for the sandblasting is 0.5 mm to 1.2 mm, and the hardness of the sand is ≥HRC60; or In S3, before placing the metal reinforcement material, the method further includes: spraying adhesive on the surface of the metal reinforcement material.

10. A rubber material for battery electrode rolling, characterized in that: The invention comprises the shock-absorbing rubber material according to any one of claims 1 to 6 or the shock-absorbing rubber material prepared by the method for preparing the shock-absorbing rubber material according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Damping rubber material with low hardness, high-temperature static torque and good durability and preparation method thereof

    CN102702588A

  • Rolling device for lithium battery production

    CN109378445A

  • Marine steel mesh core damping rubber plate and preparation method thereof

    CN109679177A

  • Rubber-blended compatibilizer, preparation method thereof and heat-resistant rubber material

    CN117720735A

  • Light, thin, warm-keeping and temperature-adjusting modified polymer aerogel composite material and preparation method thereof

    US11912872B1